EFEKTIVITAS PENGGUNAAN EXTRAORAL SUCTION DI PRAKTIK KEDOKTERAN GIGI PADA MASA PANDEMI COVID-19 - Virlia Putri Rachmayani; Raden Harry Dharmawan Setyawardhana; Norlaila Sarifah; Isnur Hatta; Muhammad Yanuar Ichrom Nahzi (Dentin, 2024)
Background: SARS-CoV-2 or coronavirus is a new virus that infects the respiratory system in humans. The spread of COVID-19 occurs through the transmission of aerosol particles produced when an infected person exhales, speaks, voices, sneezes, and coughs. Standard protective measures in dental practices are less effective at preventing the spread of COVID-19. A tool to prevent the spread of aerosols is extraoral suction (EOS) which is used to suction droplets and aerosols around the patient's mouth during dental treatment. Purpose: To find out various research articles related to the effectiveness of using extraoral suction in dental practice during the COVID-19 pandemic. Methods: All articles reviewed were obtained through Google Scholar, Pubmed, Science Direct, and Wiley Online Library with a maximum time of article publication in the last 5 years. Results: From the results it was found that the range of contamination before using extraoral suction was the lowest 0.06, and the highest 2.9. The range of contamination after using extraoral suction is the lowest 0.005, and the highest 0.8. Conclusion: The use of extraoral suction can be an effective additional alternative to reduce the amount of aerosols in dental practices during the COVID-19 pandemic.Keywords: extraoral suction, dental practice, COVID-19 pandemic. ABSTRAKLatar Belakang: SARS-CoV-2 atau corona virus adalah virus baru yang menginfeksi sistem pernapasan pada manusia. Penyebaran COVID-19 terjadi melalui transmisi partikel aerosol yang dihasilkan ketika seseorang yang terinfeksi menghembuskan napas, berbicara, bersuara, bersin dan batuk. Tindakan perlindungan standar di praktik dokter gigi kurang efektif untuk mencegah penyebaran COVID-19. Alat untuk mencegah terjadinya penyebaran aerosol yaitu extraoral suction (EOS) yang digunakan untuk menghisap droplet dan aerosol di sekitar mulut pasien selama perawatan gigi.Tujuan: Mengetahui berbagai artikel penelitian yang berhubungan dengan efektivitas penggunaan extraoral suction di praktik kedokteran gigi selama pandemi COVID-19. Metode: Seluruh artikel yang di-review didapatkan   melalui Google Scholar, Pubmed, Science Direct, dan Wiley Online Library dengan rentang waktu penerbitan artikel maksimal 5 tahun terakhir. Hasil: Dari hasil didapatkan rentang kontaminasi sebelum menggunakan extraoral suction paling rendah yaitu 0,06 dan paling tinggi yaitu 2,9. Rentang kontaminasi sesudah menggunakan extraoral suction paling rendah yaitu 0,005 dan paling tinggi yaitu 0,8. Kesimpulan: Penggunaan extraoral suction dapat menjadi alternatif tambahan yang efektif untuk mengurangi jumlah aerosol di praktik kedokteran gigi selama masa pandemi COVID-19.